Students' Mathematical Connection Ability on the Material of Volume of Cubes and Blocks in View of Keirsey's Personality Type (Unnes Journal of Mathematics Education Research, 2022)
The purpose of this study was to describe students' mathematical connection abilities in terms of Keirsey's personality type. This type of research is descriptive qualitative. The research subjects consisted of 36 fifth grade students at SDN Petompon 02 Semarang. Data collection techniques in this study were tests, observations, and interviews. The test results were analyzed, namely the indicator of mathematical connection ability refers to the NCTM indicator (2000). Data analysis was carried out with the following steps: reduction stage, presentation stage, and conclusion stage. The results of the study found that: (1) out of 36 students there were 11 artisan, 10 guardian, 7 idealist, 7 rational, and 1 artisan-guardian; (2) each personality type has various mathematical connection abilities, as well as the ability of mathematical connections within a personality also varies. For example, students with the idealist are generally able to master the three indicators of connecting between topics in mathematics, connecting mathematical concepts with other disciplines, but there are also some who fail to relate mathematics to everyday life.